Dietary Management for Adolescents with Prader–Willi Syndrome - Miller JL; Tan M (Dove Medical Press, 2020)
Jennifer L Miller, Michael Tan Department of Pediatrics, University of Florida, Gainesville, FL 32610, USACorrespondence: Jennifer L MillerDivision of Endocrinology, Department of Pediatrics, University of Florida, 1600 SW Archer Road, Box 100296, Gainesville, FL 32610, USATel +1 352 265-7337Fax +1 352 627-4415Abstract: Prader–Willi syndrome (PWS) is a complex, multisystem neurodevelopmental disorder affecting approximately 1 in 25,000 live births. PWS is caused by absence of expression of paternally inherited imprinted genes on chromosome 15q11-q13. The syndrome typically occurs due to one of three genetic mechanisms: paternal deletion of involved genes, maternal uniparental disomy, or imprinting center defects. These genetic anomalies lead to well-described clinical phenotype that includes hypotonia, hypothalamic dysfunction, social and behavioral issues, life-threatening hyperphagia, and elevated probability of obesity. Adolescents with PWS are at the highest risk for development of life-threatening obesity due to increased access to food, decreased physical activity, and hyperphagia. Currently, the only treatment for the hyperphagia is environmental control, including locked kitchens and continuous supervision of the affected individual. Caloric intake must be restricted to prevent obesity, which subsequently increases the hunger drive even more. Research and clinical practice have demonstrated that increasing physical activity along with insuring a well-balanced, nutritionally dense diet can improve overall weight control in adolescents with PWS.Keywords: Prader-Willi syndrome, diet, obesity, nutrition